Nelson Mandela and the Genesis of the ANC's Armed Struggle: Notes on Method. Issue 1 (2nd January 2018) - Simpson, Thula
Abstract : Was Nelson Mandela a member of the South African Communist Party (SACP) at the time that he formed Umkhonto we Sizwe (MK)? Was he dishonest in not revealing that he established MK at the SACP's behest? Did the African National Congress (ANC) ever grant Mandela the authority to launch an armed struggle? And, in leading the turn to violence, did Mandela strive to marginalise ANC president-general Albert Luthuli? These are the questions that have made the literature on the origins of the ANC's armed struggle a field of rich controversy in recent years. If the claims are true, they would require a fundamental reappraisal of the life and legacy of one of the most respected political figures of the 20th century. They would also rehabilitate some of the charges levelled at Mandela and the ANC by their foes during the liberation struggle. For these reasons, interest in the controversy over these questions has spread far beyond academic circles. This article clarifies the terms of the debate. It does so by laying out the arguments of the protagonists on both sides, and discussing the extent to which the archival evidence supports the various interpretations that have been offered. In the process, it revisits the circumstances and conditions under which the revolutionary underground operated in the early 1960s, thereby making a historical as well as a historiographical contribution. The article as a whole is a ground-clearing exercise that outlines the limits imposed by the existing sources on what we are able to say regarding the origins of the armed struggle, while also identifying certain methodological principles emerging from these disputes that will need to be borne in mind by future contributors to the literature.